Exploring Book-Tax Differences, Analyst Coverage, and Forecast Optimism: An Empirical Study - Yuan, Xiaoli; Lin, Wenguang (Journal of Accounting and Finance, 2023)
This research explores the relationship between book-tax differences (BTD) and the coverage of financial analysts, as well as how these two factors relate to optimistic forecasts. By evaluating how BTD affects analyst coverage, this research expands on earlier studies and finds a negative link. Additionally, it demonstrates that greater BTD indicates a higher probability of earnings manipulation, leading analysts to have a more pessimistic view of their predictions for such organizations. This research contributes to a better understanding of financial markets by shedding light on analyst behavior, financial reporting, and the complex dynamics underlying BTD in determining analyst estimates.